1997
DOI: 10.1001/archsurg.1997.01430330082014
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Embolization for Bleeding Pseudocysts Complicating Chronic Pancreatitis

Abstract: The immediate effectiveness of arterial EMB is undeniable but depends on the expertise of the radiologist. When EMB is successful, further surgery should be reserved for patients in good general condition who have other complications of chronic pancreatitis that are not amenable to minimally invasive techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 31 publications
1
85
0
2
Order By: Relevance
“…Endovascular techniques such as transcatheter embolization are an alternative to surgery and are considered the treatment of choice for arterial pseudoaneurysms by some authors (25)(26)(27). Another technique for treatment of pseudoaneurysms is percutaneous occlusion with image-guided thrombin injection.…”
Section: Embolization Of Splenic Artery Pseudoaneurysmsmentioning
confidence: 99%
“…Endovascular techniques such as transcatheter embolization are an alternative to surgery and are considered the treatment of choice for arterial pseudoaneurysms by some authors (25)(26)(27). Another technique for treatment of pseudoaneurysms is percutaneous occlusion with image-guided thrombin injection.…”
Section: Embolization Of Splenic Artery Pseudoaneurysmsmentioning
confidence: 99%
“…(2,9,11,18) Gambiez et al (19) presented in his study that the majority of his patients were surgically treated and no signs of recurrent bleeding were present after definitive pancreatic surgery. He also concluded that angiographic methods might associate other severe complications such as necrosis of the duodenum or the development of spleen abscesses.…”
Section: Discussionmentioning
confidence: 95%
“…In several recent reports, embolization is advocated as the sole therapy for the treatment of pancreatitis associated pseudoaneurysms with high technical success rates (75-100%) and low morbidity (14-25%) and death rates (0-14%) [7].…”
Section: Discussionmentioning
confidence: 99%